Hubungan Penerapan Plant-Based Diet Dalam Penurunan Risiko Hipertensi: Review - Widya Astuti; Dwikani Oklita Anggiruling (Program Studi Gizi UNSIKA, 2022)
The prevalence of non-communicable diseases (NCD) increases continuously everyyear and this is the biggest factor causing death. Based on WHO data in 2020, 73% of deaths inIndonesia were caused by NCD. Hypertension belongs to NCD and the main cause of death inthe world. The consumption pattern of the plant-based diet contains a lot of fiber, magnesium,folic acid, Fe3+, vitamins C and E, n-6 polyunsaturated fatty acids (PUFA), antioxidants,carotenoids, flavonoids, and other phytochemicals so can prevent hypertension. The purpose ofthis article was to find out the benefits of implementing a plant-based diet in reducing the risk ofhypertension, based on the results of research that has been performed. The method used inthis article is randomized control trials (RCTs) on articles published with sources from GoogleSchoolar, PubMed, and Elsevier. The results of the review showed that there was a significantrelationship in the application of the plant-based diet to the reduction of blood pressure and therisk of hypertension in various age groups. However, the application of a plant-based diet cancause micronutrient deficiencies. Therefore, the application of a plant-based diet was good forpreventing the risk of hypertension and accompanied by the selection of various types of food. Keywords : hipertensi, plant-based diet, vegetarian diet